Impact of Previous Pulmonary Tuberculosis on Chronic Obstructive Pulmonary Disease: Baseline Results from a Prospective Cohort Study - Wang, Yide; Li, Zheng; Li, Fengsen (Combinatorial Chemistry & High Throughput Screening, 2023)
Objective: Pulmonary tuberculosis (PTB) is a significant risk factor for COPD, and Xinjiang, China, has a high incidence of pulmonary tuberculosis. The effects of tuberculosis history on airflow restriction, clinical symptoms, and acute episodes in COPD patients have not been reported in the local population. Besides, the exact relationship between lung function changes in people with a history of tuberculosis and COPD risk is not clear. Methods: This study is based on the Xinjiang baseline survey data included in the Natural Population Cohort Study in Northwest China from June to December, 2018. Subjects' questionnaires, physical examination, and lung function tests were performed through a face-to-face field survey to analyze the impact of previous pulmonary tuberculosis on local COPD. Furthermore, we clarified the specific relationship between pulmonary function decline and the probability of developing COPD in people with a history of tuberculosis. Results: A total of 3249 subjects were eventually enrolled in this study, including 87 with a history of tuberculosis and 3162 non-TB. The prevalence of COPD in the prior TB group was significantly higher than that in the control group (p-value = 0.005). First, previous pulmonary tuberculosis is an essential contributor to airflow limitation in the general population and patients with COPD. In all subjects included, pulmonary function, FEV1% predicted (p-value < 0.001), and FEV1/FVC (%) (p-value < 0.001) were significantly lower in the prior TB group than in the control group. Compared to non-TB group, FEV1% prediction (p-value = 0.019) and FEV1/FVC (%) (p-value = 0.016) were found to be significantly reduced, and airflow restriction (p-value = 0.004) was more severe in prior TB group among COPD patients. Second, COPD patients in the prior TB group had more severe clinical symptoms. Compared with no history of tuberculosis, mMRC (p-value = 0.001) and CAT (p-value = 0.002) scores were higher in the group with a history of tuberculosis among COPD patients. Third, compared with the non-TB group, the number of acute exacerbations per year (p-values = 0.008), the duration of each acute exacerbation (p-values0.004), and hospitalization/ patient/year (p-values<0.001) were higher in the group with a history of tuberculosis among COPD patients. Finally, a dose-response relationship between FEV1/FVC (%) and the probability of developing COPD in people with previous pulmonary TB was observed; when FEV1/FVC (%) was < 80.8, the risk of COPD increased by 13.5% per unit decrease in lung function [0.865(0.805, 0.930)]. Conclusion: COPD patients with previous pulmonary tuberculosis have more severe airflow limitations and clinical symptoms and are at higher risk for acute exacerbations. Furthermore, lung function changes in people with a history of tuberculosis were associated with a dose-response relationship with the probability of developing COPD.
Keywords: COPD